Serum Matrix Metalloproteinases and Risk of Urologic Cancers: A Bidirectional Mendelian Randomization Study - BoWen Yang; XiaoYu Zeng; HanYu Wang; JiuHuan Feng; ShuFang Hou (American Journal of Men's Health)
Many observational epidemiological studies have reported an association between matrix metalloproteinases (MMPs) and urologic cancers. However, the causal relationship between these two phenotypes remains uncertain. This study aims to examine the bidirectional causal relationship between serum MMPs and three urologic cancers: kidney, prostate, and bladder cancer. Using data from large-scale genome-wide association studies (GWAS), we employed two-sample Mendelian randomization (MR) methods to assess the causal relationship between serum MMPs and urologic cancers. We performed inverse variance-weighted MR as the primary method for calculating the overall effects of multiple instruments, while implementing additional MR methods and sensitivity analyses. Odds ratios (ORs) were employed to evaluate the causal relationship between serum MMPs and urologic cancers risk. Our findings indicated a causal relationship between serum MMP-3 levels and prostate cancer risk (OR = 1.07, 95% confidence interval [CI] = [1.02, 1.11], p = .003). There was a possible causal relationship between serum MMP-1 and prostate cancer (OR = 0.95, 95% CI = [0.92, 0.99], p = .02). Serum MMP-1 may also increase the risk of bladder cancer (OR = 1.24, 95% CI = [1.04, 1.49], p = .016). We did not find significant associations of the remaining MMPs with prostate, bladder, and kidney cancer. In reverse MR, no significant results were observed supporting the effect of urologic cancers on MMPs ( p > .05). Our study provides evidence of a potential causal relationship between serum MMPs and both prostate cancer and bladder cancer. However, large-scale studies are necessary to confirm and reveal the underlying mechanisms of this association.